Studies on Integrated Nutrient Management in Hybrid Rice (Oryza sativa L.) under Old Alluvial Zone of West Bengal, India - Mandal, Nakul; Barik, Arun Kumar; Roy, Ashis Kumar Singha; Ghosh, Pritam; Saha, Biswajit (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted during kharif seasons of 2014 and 2015 at Instructional Farm of Dakshin Dinajpur Krishi Vigyan Kendra, Uttar Banga Krishi Viswavidyalaya, Majhian, Patiram, Dakshin Dinajpur, West Bengal, India located at 25031' N latitude and 88076' E longitude and at an altitude of 15 m above mean sea level to study the effect of integrated nutrient management on growth attributes, yield attributes, yield and economics of hybrid rice (Oryza sativa L.). The experiment, consisted of ten treatments, was laid out in Randomised Block Design where each treatment was replicated thrice. The test crop was grown following recommended package of practices. Standard statistical methods were followed for analysing the experimental data. Integrated nutrient management in hybrid rice significantly influenced growth attributes, yield attributes, yield and economics of hybrid rice. Application of 75% recommended dose of nitrogen (RDN) from urea+25% RDN from dhaincha green manure exhibited highest growth attributes, yield attributes, grain yield (5.74 t ha-1), straw yield (6.59 t ha-1), gross return (Rs. 95175 ha-1 ) and net return (Rs. 52541 ha-1) from hybrid rice. However, this was at par with the application of 100% RDN from urea followed by 75% RDN from urea+25% RDN from mustard oil cake. The highest return per rupee investment was achieved from 100% RDN from urea (Rs. 2.25) though this was similar with 75% RDN from urea+25% RDN from dhaincha green manure (Rs. 2.23).